2003
DOI: 10.1016/s1521-6926(02)00096-8
|View full text |Cite
|
Sign up to set email alerts
|

Maternal thrombophilia and neonatal thrombosis

Abstract: In neonates and infants, numerous clinical and environmental conditions lead to elevated thrombin generation and subsequent thrombus formation. Genetic prothrombotic defects (protein C, protein S and antithrombin deficiency, mutations of coagulation factor V and factor II, elevated lipoprotein (a)) have been established as risk factors of thromboembolic events in neonates and infants. The interpretation of the laboratory evaluation relies on age-dependent normal reference values. Because appropriate clinical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 75 publications
0
13
0
1
Order By: Relevance
“…Heller and colleagues recommended that neonates with TE should undergo an extensive screening, including resistance to activated protein C (APC-R), protein C, protein S, and antithrombin activity, concentration of clottable fi brinogen, plasminogen activity, activities of coagulation factors VIIIC and XII, Lp(a), histidine-rich glycoprotein, heparin cofactor II, antiphospholipid antibodies, lupus anticoagulants, as well as fasting homocysteine concentrations. In addition, DNA-based assays (ie, factor V G1691A mutation, factor II G20210A variant and MTHFR C677T genotype) should be performed (Heller and Nowak-Gottl 2003). Whereas DNA-based mutation analysis can be performed at any time point, protein-based assays should not be carried out in the fi rst 6-8 months after the event and oral anticoagulation is recommended to be discontinued at least 14-30 days before plasma samples for thrombophilia diagnosis are drawn (Heller and Nowak-Gottl 2003).…”
Section: Congenital Thrombophiliamentioning
confidence: 99%
See 2 more Smart Citations
“…Heller and colleagues recommended that neonates with TE should undergo an extensive screening, including resistance to activated protein C (APC-R), protein C, protein S, and antithrombin activity, concentration of clottable fi brinogen, plasminogen activity, activities of coagulation factors VIIIC and XII, Lp(a), histidine-rich glycoprotein, heparin cofactor II, antiphospholipid antibodies, lupus anticoagulants, as well as fasting homocysteine concentrations. In addition, DNA-based assays (ie, factor V G1691A mutation, factor II G20210A variant and MTHFR C677T genotype) should be performed (Heller and Nowak-Gottl 2003). Whereas DNA-based mutation analysis can be performed at any time point, protein-based assays should not be carried out in the fi rst 6-8 months after the event and oral anticoagulation is recommended to be discontinued at least 14-30 days before plasma samples for thrombophilia diagnosis are drawn (Heller and Nowak-Gottl 2003).…”
Section: Congenital Thrombophiliamentioning
confidence: 99%
“…In addition, DNA-based assays (ie, factor V G1691A mutation, factor II G20210A variant and MTHFR C677T genotype) should be performed (Heller and Nowak-Gottl 2003). Whereas DNA-based mutation analysis can be performed at any time point, protein-based assays should not be carried out in the fi rst 6-8 months after the event and oral anticoagulation is recommended to be discontinued at least 14-30 days before plasma samples for thrombophilia diagnosis are drawn (Heller and Nowak-Gottl 2003).…”
Section: Congenital Thrombophiliamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, acquired prothrombotic risk factors like hyperhomocystenemia, increased lipoprotein a and acquired antiphospholipid antibodies and lupus anticoagulant play a role 13 15 3537. However, the contribution of genetic or acquired thrombophilia in the causation of thrombosis in the preterm infant is unknown.…”
Section: Systemic Thrombosismentioning
confidence: 99%
“…Heller and colleagues have suggested that tests based on DNA mutation analysis (such as factor V Leiden or methylene tetrahydrofolate reductase, MTHFR) can be performed at any age. Protein-based assays should be delegated to be done at ∼6 months of age [21]. Certainly, when thrombophilia workup is performed in the neonatal period for protein-based assays, it should be repeated at a later age.…”
Section: Role Of Thrombophilia Workup In the Neonatal Periodmentioning
confidence: 99%